Middle-class Household Consumption in Dhaka, Bangladesh: Understanding Current Practices Related to Food, Electricity, Transport and Attire - Solaiman, Mohammad (Curtin University, 2019)
Dhaka experiences unplanned expansion and large population influx. Half of its dwellers are well-educated with stable employment, forming the city’s middleclass. Amid growing concerns over Dhaka’s liveability, the consumption practices of this middleclass related to food, attire, transport and energy are explored using a household survey and expert interviews. The Theory of Planned Behaviour explains the current unsustainable patterns resulting from Dhaka’s socio-historical formation, economic development and globalisation. Changing social norms can improve its future.